Yeats and revisionism a half-century of the dancer and the dance - O'Hara, Daniel T. 1948- (Anthem Press, 2023)
The publication collects Daniel T. O'Hara's half century of essays and review-essays on Yeats and his major poetry and drama and how leading critics and theorists have sought to revise their reception for their periods of time and indeed for the future. Its aim is to trace a critical history of the last fifty years, even as it opens the prospects for the future of critical reading of Yeats and modern poetry
Also issued in print: 2023. - Includes bibliographical references and index
Keywords: Yeats, W. B. / (William Butler) / 1865-1939 / Criticism and interpretation; Yeats, William Butler -- 1865-1939